PELATIHAN PEMBUATAN JAMU DARI DAUN KARAMUNTING DI DESA BURAI, TANJUNG BATU, OGAN ILIR - Salni Salni; Juswardi Juswardi; Endri Junaidi; Nita Aminasih; Singgih Tri Wardana; Poedji Loekitowati Hariani (Universitas Mataram, 2022)
Diabetes mellitus is a degenerative disease characterized by insulin deficiency. The number of people with diabetes in Indonesia has increased and spreads throughout all Indonesia regions. Dependence on modern drugs (synthetic drugs) often causes side effects. Indonesia has various types of plants that are possible to prevent and treat diabetes mellitus. One of the plants that can reduce sugar levels while preventing and increasing body stamina is karamunting leaf (Rhodomyrtus tomentosa (Ait.) Hassk). Therefore, this community service activity aims to provide counseling about degenerative diseases, how to treat and prevent them. The activity also also provides training on how to make herbal medicine from karamunting leaves. The activity was carried out in Burai village, Tanjung Batu sub-district, Ogan Ilir district. The target audience is 36 people, some of them are diabetics. The activities support with health workers to check blood sugar levels. There are 3 types of training on making herbal medicine from karamunting leaves, namely: (i) karamunting leaf powder, (ii) karamunting leaf powder, with the addition of turmeric powder, ginger and (iii) spices consisting of karamunting leaves, ginger, turmeric, secang, lemongrass, lime leaves and rock sugar. The results of the level of preference test, the type of herbal medicine 3 were the most preferred. The evaluation results showed that as many as 83.3% of the target audience could explain the manufacture of herbal medicine from karamunting correctly, as many as 86.1% had consumed herbal medicine from karamunting leaves, and 90.3% of the audience wished to continue consuming herbal medicine from karamunting either to lower blood sugar levels or reduce blood sugar levels, for prevention and increase stamina. Making herbal medicine from karamunting increases public knowledge about diabetes mellitus, prevention efforts and increases body stamina.